Determination of heavy metal accumulation in Ipomea aquatica using microwave digestion method - Nabila Syazreen, Abdul Razak (2010)
For several decades, farmers have been applied landfill materials as fertilizer to their fields. The aim of this study is to compare the heavy metal uptakes by Ipomea Aquatica with both types of the soil cultivated (from Ulu Tualang and from market) and to predict whether the plants cultivated could be used as food and feed. The concentrations of heavy metals in plant cultivated in soil taken from Ulu Tualang and from market were tested with the standard laboratory method by using atomic absorption spectrophotometer (AAS). Sample preparation was conducted by using microwave digestion method. High recovery values of spiked samples confirmed that microwave digestion method gives the best and most accurate result where Pb (9.18 and 9.55 mg/kg) appeared to be the most abundant metal while Mn exhibited the lowest abundance (2.57 and 2.95 mg/kg). It was found that some metal content in Ipomea Aquatica (Cd, Cr, and Pb) showed that it had over the maximum limit permitted by WHO. Hence, it is suggested that fertilizers used by farmers should be tested first before being used for plantation purpose. Hence, on the basis of present study, the best possible treatment of soil and fertilizer used in cultivating plants is to remove the sources of those elements of heavy metals in the environment.